Cellular RNA Helicase DDX1 Is Involved in Transmissible Gastroenteritis Virus nsp14-Induced Interferon-Beta Production - Zhou, Yanrong; Wu, Wei; Xie, Lilan; Wang, Dang; Ke, Qiyun; Hou, Zhenzhen; Wu, Xiaoli; Fang, Ying; Chen, Huanchun; Xiao, Shaobo; Fang, Liurong (Frontiers in Immunology, 2017)
Transmissible gastroenteritis virus (TGEV), an enteropathogenic coronavirus (CoV) of porcine, causes lethal watery diarrhea and severe dehydration in piglets and leads to severe economic losses in the swine industry. Unlike most CoVs that antagonize type I interferon (IFN) production, previous studies showed that TGEV infection induces IFN-I production both in vivo and in vitro. However, the underlying mechanism(s) remain largely unknown. In this study, we found that TGEV infection significantly facilitated IFN-β production as well as activation of the transcription factors IFN regulatory factor 3 (IRF3) and nuclear factor-kappaB (NF-κB) in porcine kidney (PK-15) cells. Screening of TGEV-encoded proteins demonstrated that nonstructural protein 14 (nsp14) was the most potent IFN-β inducer and induced IFN-β production mainly by activating NF-κB but not IRF3. Further analysis showed that nsp14 interacted with DDX1, a member of the DExD/H helicase family. Knockdown of DDX1 by specific siRNA significantly decreased nsp14-induced IFN-β production and NF-κB activation. Furthermore, TGEV-induced IFN-β production and IFN-stimulated gene (ISG) expression were decreased in cells transfected with DDX1-specific siRNA, indicating the vital role of DDX1 to TGEV-induced IFN-β responses. In summary, our data revealed a potential coactivator role of host RNA helicase DDX1 to the induction of IFN-β response initiated by TGEV and demonstrated that nsp14 is an important IFN-inducer among the TGEV-encoded proteins.